Modeling and Static Analysis of Pressure Vessel in Full Welded Connections - Lydia Anggraini (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2023)
The pressure analysis on the cylindrical pressure vessel is simulated computationally with the finite element method and evaluated from some point of view performance parameters. In this study, the stress elastic analysis method is used with basic calculations to determine the design thickness of the shell, head, nozzle, and material specifications used for pressure vessel analysis. For contraction design by using Autodesk Inventor software for 3D models. This analysis used the finite element method with ANSYS Workbench software, including thermal transient analysis of welded joints then connected with structural analysis of analysts for construction design. It includes material properties and weld joint design on each part of the overall pressure vessel. This result can be used to more rapidly identify critical design variables to optimize the design and find out the maximum deformation occurring in each part of the pressure vessel. The resulting analysis leads to the selection of appropriate measurements for structural use and thermal transient heat transfer analysis on the weld joints on the adjacent welding Nozzle. Interconnect and overlap welded joints with manhole pad welding and identification of the most critical deformation measurements based on parameters.